(untitled) (Journal of Medical & Health Sciences Review, 2025)
This study aimed to assess the knowledge and perceptions of mothers regarding child immunization in a community to evaluate the awareness, understanding and perceptions of mothers about early vaccination and to recommend the measures to improve their awareness status about immunization. A simple descriptive survey was carried out for the purpose to assess the knowledge and perceptions of mothers regarding immunization. A sample of 80 mothers was taken in the study by non-probability convenience sampling method. Microsoft Excel Software and SPSS 22 was used for data entry and analysis. The findings of the study showed that majority of the mothers were fully or partially aware about the early immunization yet some of them were ignorant in this regard. More than (75%) of the mothers were in favour to be educated about the immunization and its importance in regard to prevent early childhood diseases. They strongly suggested that awareness sessions should be conducted for mothers to comply with the early immunization In conclusion, it is strongly suggested that education and immunization information must be instructed to the public by awareness sessions (teachings) as well as by the information given by vaccinators and Lady Health Workers. The education level of females should be improved and mothers’ knowledge of immunization must be enhanced.